Willingness To Pay for Conservation and Sustainability of Lenggong Valley as World Heritage Site (WHS) - Shariffah Nor Fazlin, Syed Mustapha; Dayang Affizzah, Awang Marikan; Nor Afiza, Abu Bakar (ERA, 2024)
According to archaeologists, Lenggong Valley (LV) is linked to the earliest known human inhabitant in Southeast Asia as well as the region's only thoroughly documented prehistoric human skeleton. It is important although, since it was only named a World Heritage Site (WHS) in June 2012. Thus, not much of the people are aware of the importance of maintaining the heritage site. As for LV, lacking in maintenance is the main issues that contribute to the lack of maintenance. Due to lack of maintenance has led to some issues where the UNESCO can remove LV as the WHS in the UNESCO list. Therefore, the understanding of local people and tourist can help in the success of the future conservation and sustainability within the area. The main objective of this study is to examine the economic values that local people are willing to pay to visit LV, Perak. While the specific objective of this research is to investigate the local community engagement and perception towards the importance LV as WHS. Next, is to determine